The Relationship of the Growth of the Construction Sector with the Value of Urban Land in the Commercial Axis Coronel Mendoza de Tacna by 2020 - Espinoza Vidaurre, Sam M. (2022)
This article aims to analyze the relationship between the economic growth of the construction sector with the increase in the value of urban land, in the commercial axis of Coronel Mendoza in Tacna by 2020, for which it has been established as a hypothesis that there is a direct positive link between the growth of the construction sector and the value of urban land, based on the field information obtained with the application of the PER Model (Pressure, State, Response) that allowed the identification of symptoms and causes, as well as the consultation of primary sources of regulatory entities or state agencies, under a descriptive and correlational research design. The main results of the Central Reserve Bank of Peru (BCR, 2019) indicate that “the growth of the GDP of the construction sector, whose index is 3.8%, influences the tariff value of the properties in the commercial axis of Coronel Mendoza , with an increasing increase of 5%, in the minimum value, and 30% in the annual maximum value ”. Real estate for commercial activity in the study sector represents 47.90% of urban land and 1.02% of urban land in Tacna province, however, the increase in commercial use has been expressed by 15% in the last year , while residential use has decreased by 19%; on the other hand, the construction sector grew by 5.04% annually, thus demonstrating that the growth of the construction sector affects the increase in the value of urban land in the commercial axis under study.